(untitled) (Web of Teachers: Inderscience Research, 2025)
In today’s world, effective methods for developing speaking skills are increasingly important. This research explores the role of Task-Based Language Teaching in enhancing oral communication among students and highlights the significance of this approach. Hilma Safitri, Zainal Rafli, and Devanti (2019) conducted research on enhancing speaking competence and building confidence among students through task-based learning activities. Other Western researchers have explored similar approaches with high school students, employing task-based activities such as monologues and dialogues to facilitate conversations on various topics. This highlights that speaking is not only about daily conversations but also about expressing opinions on diverse subjects (Afria Nita, Yenni Rosimella, Ratmanida, 2019). The significance of this method lies in its student-centered approach, which fosters communicative skills through group debates where students express their agreement or disagreement on various topics. These interactive activities form the foundation of task-based teaching. Our findings indicate that engaging in oral communication through open-sharing tasks helps students become more confident while enabling them to share ideas on various topics. This approach enhances their critical thinking skills, particularly in relation to controversial opinions, and promotes effective communication. The target audience for this research consists of senior high school students. The study was conducted over four weeks with 10th and 11th grade students from Uzbekistan. Throughout this period, the research assessed both successes and challenges.